THE PERCEIVED VALUE OF THE TEC WEEK IN THE DEVELOPMENT OF TRANSVERSAL COMPETENCES (Proceedings of the International Conference on Education, 2021)
Currently, educational institutions have the challenge of graduating students as experts in their disciplines who have a series of competencies that will allow them to assimilate their professional identity. Tecnológico de Monterrey established the Tec Week as a mandatory framework to close the gap between academic courses and student affairs activities to develop transversal competences. Those cross-cutting competences integrate knowledge, skills, and attitudes relevant to responding, leading, and transforming an uncertain future. The present study aimed to determine the Tec Week's value in professional identity formation phases considering transversal competences There was applied a quantitative, descriptive, trans-sectional, and not experimental method. Participants were first-year students from several academic programs. A pre-test and post-test self- perception instruments were adapted from Olivares et al. (2019) to compare expectations (pre-test) from achievements (post-test) as proposed by the Expectations Confirmation Theory. Results showed that Tec Week offers development for Self-concept, Wellness and Self-awareness, Collaboration, and Diversity. The results encourage incorporating activities such as Tec Week to impact students' professional identity formation for self-care and socialization, considering an inclusive socialization environment and healthy relations during their first years.
Keywords: Professional Identity Formation; Transversal Competences; Self-concept; Self-care; higher education